2023
DOI: 10.3389/fncom.2023.1119685
|View full text |Cite
|
Sign up to set email alerts
|

Predictive neuromodulation of cingulo-frontal neural dynamics in major depressive disorder using a brain-computer interface system: A simulation study

Abstract: IntroductionDeep brain stimulation (DBS) is a promising therapy for treatment-resistant major depressive disorder (MDD). MDD involves the dysfunction of a brain network that can exhibit complex nonlinear neural dynamics in multiple frequency bands. However, current open-loop and responsive DBS methods cannot track the complex multiband neural dynamics in MDD, leading to imprecise regulation of symptoms, variable treatment effects among patients, and high battery power consumption.MethodsHere, we develop a clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…Extending our adaptive estimator to simultaneously estimate the linear matrix parameters online and completely remove the offline model fitting experiment is another direction that requires further investigation [71][72][73]. Third, there are rich explorations of effective feedback signals and closed-loop neuromodulation treatments for other neurological and neuropsychiatric disorders such as epilepsy [74][75][76] and major depression [39,77,78]. Our robust adaptive DBS control framework is flexible to model different types of input DBS parameters and output neural activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending our adaptive estimator to simultaneously estimate the linear matrix parameters online and completely remove the offline model fitting experiment is another direction that requires further investigation [71][72][73]. Third, there are rich explorations of effective feedback signals and closed-loop neuromodulation treatments for other neurological and neuropsychiatric disorders such as epilepsy [74][75][76] and major depression [39,77,78]. Our robust adaptive DBS control framework is flexible to model different types of input DBS parameters and output neural activity.…”
Section: Discussionmentioning
confidence: 99%
“…where C † = (CC T ) −1 C is the pseudo-inverse, or a more sophisticated dynamic Kalman estimator [38][39][40].…”
Section: Linear Dbsmentioning
confidence: 99%
“…Closed-loop BCI with predictive neuromodulation has also been used to treat MDD with improved efficacy compared to standard non-BCI neuromodulation methods. The system predicts the non-linear and multiband neurodynamics in MDD and can manage and control the diseased neural dynamics to effectively produce a therapeutic output signal [133] . Additionally, BCI has been shown to improve ET outcomes, as the use of dBCI in ET has diminished the total stimulation applied since it can disable neural stimulation when the patient is not actively using their limbs.…”
Section: Other Lesioningmentioning
confidence: 99%
“…where C † = (CC T ) −1 C is the pseudo-inverse, or a more sophisticated dynamic Kalman estimator [46,47,48]. Simulation studies have shown that linear DBS improves over the on-off DBS for PD [31,29,27].…”
Section: Linear Dbsmentioning
confidence: 99%